Combined Effects of Curcuma xanthorrhiza Rhizome and Persea americana Leaves Extracts on Streptozotocin-Induced Diabetes in Rats - Thong, Vertirico; Ahnafani, Miyada Nur; Lestari, Helda Dwi; Ahnafani, Mayada Nur; Kurniawati, Darini (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Indonesia's rich biodiversity encompasses numerous plants with ethnomedicinal applications, including avocado (Persea americana) leaves and temulawak (Curcuma xanthorrhiza) rhizomes, traditionally used for managing diabetes mellitus. This study investigated the antidiabetic activity of a combination of C. xanthorrhiza rhizomes and P. americana leaves in streptozotocin (STZ)-induced diabetic rats. Extracts were obtained via 72-hour maceration using 96% ethanol, followed by phytochemical screening and a 3-day toxicity assessment in rats at doses of 50, 150, and 200 mg/kg BW. Diabetic rats, induced with a single intraperitoneal injection of 20 mg/kg STZ, were treated for 14 days with three different combination formulas of C. xanthorrhiza rhizome and P. americana leaf extracts: Formula 1 (0.6 g : 0.4 g), Formula 2 (0.4 g : 0.6 g), and Formula 3 (0.4 g : 0.4 g). Metformin (500 mg/kg/day) served as the positive control, and 0.5% CMC-Na was the negative control. Phytochemical analysis revealed the presence of various bioactive compounds in both extracts. No significant toxicity was observed in rats across the tested doses. The Mann-Whitney test indicated a significant difference in blood glucose levels in diabetic rats after 14 days of treatment (p=0.037). Notably, all combination formulas exhibited antidiabetic activity. Specifically, Formula 1 demonstrated comparable antidiabetic efficacy to metformin (500 mg/kg). These findings suggest that combining C. xanthorrhiza and P. americana extracts possesses significant antidiabetic potential.